Identification of gastrointestinal parasites by coproscopy in wild carnivores from the Parque de las Leyendas, Lima, Peru - Acosta Z., Maritza (2015)
The aim of this study was to identify gastrointestinal parasites in wild carnivores from the Parque de Las Leyendas Zoo in Peru by four conventional coproparasitological methods (direct, Ritchie modified Sheather and the Ziehl Neelsen method for coccidia). A total of 62 animals of 15 species from six families were sampled. Results showed that 25.8% (16/62) of the samples were positive to parasites. Panthera leo, Panthera tigris and Lycalopex sechurae were the most affected species (9/9, 2/3, and 3/5 respectively). The parasites identified were the nematode Toxascaris leonina (12/16), the acanthocephalan Corynosoma sp (3/16), the cestode Atriotaenia sp (1/6) and the protozoo Giardia sp (1/6). No significant association was found between the variables age and sex.